Effect of Storage Temperatures on Fruit Quality of Tomato (Solanum lycopersicum Mill.)Cultivated under Water Stress Treatment - , Amalya Nurul Khairi; , Dr. Affan Fajar Falah, STP, M.Agr ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tomato cultivated hydroponically under moderate water stress treatment produce better qualities such as higher sweetness (popular for âhigh brix tomatoâ) and high lycopene content. The objective of this research is to analyze the effects of storage temperatures on postharvest quality of water stress and no water stress tomato especially on weightloss, sweetness, acidity , firmness, lycopene content, and color during storage. After harvesting at early ripening stage (light red color), various temperatures (10 Â°C, 15 Â°C, 25 Â°C, and 30 Â°C) were given to water stress and no water stress tomatoes until full ripe or mature stage of tomato. Quality parameters of the fruit were measured on individualtomatoes at regular intervals. The result showed that firmness value of waterstress tomato were lower and sweetness, acidity, lycopene content, and weightloss index of water stress tomato were higher than no water stress tomato during storage with various temperature. storaging with temperature under 15 Â°C maintain firmness and weight of both no water stress and water stress tomato. Storaging with temperature above 15 Â°C increased lycopene content of water stress tomatoes. Multiple regression model were calculated to observed the correlation of each qualities parameters and make easier prediction of tomato qualities if some of simple measurements were applied. The result showed only weight and firmness model that applicable. Optimum condition to store the tomato in order to increase the lycopene was 24.52Â°C during 11 days.. the color were not significantly changed and remained stable during storage with all temperature that means if we harvest the tomato during ripening stage before wilting there is no significant color change and then slightly increase when the tomato or stable